DNA diagnosis of the fragile X syndrome in a series of 236 mentally retarded subjects and evidence for a reversal of mutation in the FMR-1 gene - van den Ouweland, A M; de Vries, B B; Bakker, P L; Deelen, W H; de Graaff, E; van Hemel, J O; Oostra, B A; Niermeijer, M F; Halley, D J (American journal of medical genetics, 1994)
The cloning of the FMR-1 gene and the identification of an expanded CGG repeat in DNA of fragile X patients has made reliable DNA diagnosis feasible. Southern blotting and PCR assays of the CGG repeat in an unselected series of 236 mentally retarded subjects resulted in the identification of 10 new fragile X families. Reevaluation of previously assessed fragile X families resulted in the first observation of the presence of a reversal of mutation in the FMR-1 gene.